Potential Relevance of Bell-Shaped and U-Shaped Dose-Responses for the Therapeutic Targeting of Angiogenesis in Cancer - Andrew R. Reynolds (SAGE Publishing, 2010)
Tumor angiogenesis, the growth of new blood vessels into tumors, facilitates tumor growth and thus represents an attractive therapeutic target. Numerous experimental angiogenesis inhibitors have been characterised and subsequently trialled in patients. Some of these agents have failed to show any substantial activity in patients. In contrast, others have been more successful, but even these provide only a few months extra patient survival. Recent work has focused on understanding the effects of anti-angiogenic agents on tumor biology and has revealed a number of new findings that may help to explain the limited efficacy of angiogenesis inhibitors. Herein, I review the evidence that hormetic dose-responses (i.e. bell-shaped and U-shaped dose-response curves) are often observed with anti-angiogenic agents. Agents reported to exhibit these types of dose-response include: 5-fluorouracil, ATN-161, bortezomib, cisplatin, endostatin, enterostatin, integrin inhibitors, interferon-α, plasminogen activator-1 (PAI-1), rapamycin, rosiglitazone, statins, thrombospondin-1, TGF-α1 and TGF-α3. Hormesis may also be relevant for drugs that target the vascular endothelial growth factor (VEGF) signalling pathway and for metronomic chemotherapy. Here I argue that hormetic dose-responses present a challenge for the clinical translation of several anti-angiogenic agents and discuss how these problems might be circumvented.